Early burst of parallel evolution describes the diversification of gecko toe pads - McCann, Jenny; Hagey, Travis J. (Frontiers in Ecology and Evolution, 2024)
Introduction Similar traits appearing in distantly related organisms have intrigued scientists for generations. While anole lizards of the Caribbean are often touted as a classic example of repeated evolution, the adhesive toe pads of gecko lizards are an equally striking yet underappreciated example of relatedly evolved traits. The strikingly diverse toe pads of gecko lizards (Gekkota) have been gained and lost multiple times throughout the clade’s evolutionary history. In addition, distantly related genera have repeatedly evolved remarkably similar morphologies. This complicated combination of divergent and repeated evolution represents a useful system for understanding the evolution of complex structures, including repeated adaptation. Methods Using geometric morphometrics, we evaluated parallel morphological differences across families and expanded existing approaches fitting models of trait evolution to use geometric morphometric data. Adapting the use of phylogenetic independent contrasts for shape data, we conducted a node height test to investigate how toe pad shape has evolved across geckos. Results We found multiple examples of significant parallel differences in toe pad morphology and support for a model of early burst morphological evolution. Discussion Our results suggest the diversification of Gekkotan toe pads included repeated parallel changes from padless ancestral morphologies to derived pad bearing morphologies. This morphological diversification occurred rapidly early in the diversification of gecko families and genera and slowed more recently, during diversification within genera.